Eccentric Target Sign in Cerebral Toxoplasmosis – neuropathological correlate to the imaging feature - Sharath Kumar, GG (2010)
Cerebral toxoplasmosis remains one of the most common focal brain lesions in patients with acquired immune deficiency syndrome (AIDS). Diagnosis is a challenge as on cranial imaging, it closely mimics central nervous system lymphoma, primary and metastatic CNS tumors or other intracranial infections like tuberculoma or abscesses. An MR imaging feature on post contrast T1 weighted sequences considered pathognomonic of toxoplasmosis is the ‘eccentric target sign’. The pathological correlate of this imaging sign has been speculative. Herein we correlate the underlying histopathology to the MR feature of ‘eccentric target sign’ in a patient with autopsy proven HIV/AIDS related cerebral toxoplasmosis. The central enhancing core of the target seen on MR imaging was produced by a leash of inflamed vessels extending down the length of sulcus that was surrounded by concentric zones of necrosis and a wall composed of histiocytes and proliferating blood vessels with impaired permeability producing the peripheral enhancing rim.